Energy use and global warming potential: evaluating diverse cropping systems. A field study in Rajshahi District in Bangladesh - Saiful Islam; Cheesman, Stephanie; Maruf Hossen Shanto; Md. Arifur Rahaman; Hossain, M. Khaled; Hossain, Shakhawat; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
The Barind Tract in the Rajshahi region of Bangladesh spans 18,4822 hectares. It is marked by challenging agroecological conditions, including high temperatures, low soil moisture retention, and erratic rainfall, leading to severe water stress. The area’s soils have poor drainage and low organic matter, resulting in suboptimal crop productivity (DAE, 2023). To address these issues, a participatory research trial was conducted from 2022 to 2023, exploring diversified, intensified, and climate-resilient cropping systems compared to traditional practices. This brief summarizes key findings on energy use, global warming potential (GWP), and emission intensity, offering insights for improving agricultural outcomes in this climate-sensitive region.